Innovation and Creativity in SMEs - Gay, Claudine; Szostak, Berangere (Wiley-ISTE, 2019)
In order to survive in their market and differentiate themselves from the competition, small- and medium-sized enterprises (SMEs), which represent more than 90% of companies worldwide, need to be creative and innovative. This book presents a conceptual framework for thinking about innovation and creativity in SMEs. It takes into account their strategic relation to their environment and the economic, technological and social changes that they face. Their ability to enhance their creativity with new ideas and to legitimize them during their implementation is also taken into account.
Online resource; Title from title page (viewed September 11, 2019)